Bilinorm administration combined with Phototherapy in the management of neonatal jaundice: a hospital based clinical trial - Hameed, Numan N. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Neonatal jaundice (NJ) is a common problem worldwide and frequent in Iraq . Several reports were published on prevalence, distribution, causes and treatment of NJ.This clinical trial was carried out to demonstrate the effect of combinations of Castrol oil, riboflavin and magnesium in mechanical elimination of bilirubin after enhancing hepatic excretion by phototherapy. Patients & methods: This clinical trial included a total of 61 significantly jaundiced neonates who were admitted to the special care baby unit of Children Welfare Teaching Hospital, medical city complex, Baghdad, Iraq, during the period June 1st to Dec.31st 2007. Phototherapy was applied alone in 30 neonates (group 1) and phototherapy with Bilinorm in 31 neonates (group 2),(Bilinorm oral gel constituted of riboflavin sodium phosphate, magnesium oxide and castor oil). Student’s t test was used to examine the differences in variables between the two groups. Results: There were no significant differences between the two groups in body weight, age of onset of jaundice, age on admission, and TSB on admission (p =0.9,0.4, 0.4, 0.4, respectively). A significant difference in total decrease in TSB was noticed between group II (7.2 ± 2.4) and group I (5.9 ± 1.8)(p = 0.02). Days of hospitalization were significantly lower in group II (2.4 ± 0.8 days) than in group I (3.3 ± 1.5 days) (p = 0.009), and hours of phototherapy were significantly lower in group II (47.4 ± 19.7 hours) than in group I (66.8 ± 27.4 hours) (p= 0.002). Conclusions: There was a statistically significant difference regarding total decrease in TSB, days of hospitalization and hours of phototherapy when both Bilinorm and phototherapy were used than when phototherapy was used alone. So mechanical elimination of bilirubin from intestinal lumen may enhance the effect of phototherapy.